Manajemen Berbasis Sekolah (MBS) dalam Konteks Pendidikan Islam - Suryadi, Toto; Yunita, Ita (ALSYS, 2025)
The limited research on the application of School-Based Management (SBM) within the context of Islamic education at the regional level forms the basis of this study, despite SBM’s strategic role in enhancing the quality and autonomy of madrasahs. This study aims to examine the implementation, supporting and inhibiting factors, and the forms of SBM models that emerge within the cultural and Islamic value framework at Madrasah Tsanawiyah. A qualitative method with a multisite case study approach was employed, involving three madrasahs (one public and two private) purposively selected. Data collection techniques included in-depth interviews, participatory observation, and document analysis of the Madrasah Work and Budget Plans (RKAM), followed by thematic analysis. The findings indicate that SBM is implemented adaptively through three main pillars: transformational leadership by the madrasah head, synergy between the school committee and foundation, and the internalization of Islamic values such as musyawarah (deliberation) and amanah (trustworthiness) in decision-making and management practices. Key challenges include limited human resource competencies, fluctuating community participation, and policy misalignment between the Ministry of Religious Affairs and private foundations. The study concludes that the success of SBM in Islamic schools is highly dependent on the integration of its principles into the institutional culture of the madrasah. The implications suggest the need to develop a context-sensitive SBM theory and design training programs tailored to the unique characteristics of madrasahs through collaborative efforts between the Ministry of Religious Affairs and private foundations.